2007
DOI: 10.1021/ma071052c
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Thin Film Characteristics of Poly(tetrafluoroethylene) Melts from Molecular Dynamics Simulations

Abstract: The surface characteristics of thin films of poly(tetrafluoroethylene) (PTFE) melts were investigated by molecular dynamics simulations, employing the recent explicit atomic force field, including partial charges, which was fine-tuned to the experimental PVT data, the chain conformation and the crystal structure (Macromolecules 2003, 36, 5331). Surface tension was calculated from the virial equation of the pressure tensor, taking into full account of the long-range correction terms, in good agreement with expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
2
9
1
Order By: Relevance
“…MD simulations were performed on melts of atactic polystyrene (PS) at 450 K, which is well above its experimental T g of 373 K, following the simulation methods described in detail in the previous studies of polymethylene films [40] and polytetrafluorene (PTFE) films [49]. The simulation box has 20 molecules and each molecule has 15 repeating units, with the stereochemical configuration of each repeat unit chosen randomly as meso or racemic [48,55].…”
Section: System Specifications and Simulation/computation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulations were performed on melts of atactic polystyrene (PS) at 450 K, which is well above its experimental T g of 373 K, following the simulation methods described in detail in the previous studies of polymethylene films [40] and polytetrafluorene (PTFE) films [49]. The simulation box has 20 molecules and each molecule has 15 repeating units, with the stereochemical configuration of each repeat unit chosen randomly as meso or racemic [48,55].…”
Section: System Specifications and Simulation/computation Methodsmentioning
confidence: 99%
“…The earlier studies showed the general features of polymer thin films and interfaces, but they had critical limitations in that they were unable to include accurate information about the detailed chemical structures of various polymers and their interactions at various surfaces. Such shortcomings have been improved by recent advances in computational capability and simulation algorithms, allowing large scale simulations on the polymer/vacuum [49] and the polymer/solid [50][51][52] interfaces with detailed consideration of explicit atomistic structures and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism leading to these structures as well as the structures by themselves are observed and characterized for the first time at atomic level. A few MD simulations on PFA or related molecules have been carried out in the past by several authors [15][16][17][18][19][20]. The closest approximations to the present work are the studies by Kim and Shin [16,17], based on 10-nslong simulations for F12H18 at several temperatures using implicit solvent.…”
Section: Introductionmentioning
confidence: 95%
“…Hariharan and Harris 23 presented a UA-based study in which their model could not capture surface-tension differences between decane and perfluorodecane. References [24][25][26] to that work 23 seem to suggest that this is caused by an inherent limitation of the UA method. However, the results in this work demonstrate that this is not the case; rather, the issue is with the specific UA model used and its parameterization.…”
Section: Resultsmentioning
confidence: 99%